2017
DOI: 10.1055/s-0036-1588458
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Cyclic Diacyl Peroxides: Reactivity and Selectivity Enhancement Brought by the Cyclic Structure

Abstract: Preliminarily studies on cyclic diacyl peroxides have shown novel and superior reactivities compared with their acyclic diacyl peroxide counterparts in many reaction types. After summarizing the methods available for the preparation of cyclic diacyl peroxides and describing their structural features, this review brings together an overview of their reactivities with respect to oxidations and decarboxylations, and demonstrates the advantages of reactions with cyclic diacyl peroxides, which include metal-free, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 21 publications
(17 reference statements)
0
9
1
Order By: Relevance
“…Inspired by the enzyme-catalyzed oxidative halogenation in nature and our continuing interest and efforts in the utilization of cyclic peroxides, we are intrigued by the possibility of complementing the existing Hofmann–Löffler–Freytag-type processes by the combination of cyclic diacyl peroxides and diverse halide salts. We speculated that such proposed halogenating reagents (Figure ) could increase the efficiency of Hofmann–Löffler–Freytag-type reactions by two potential pathways: increasing the reactivity of halogenating reagent by the existence of the intramolecular benzoates, or influencing the conformation of the substrates to favor reactivity and selectivity by intermolecular force.…”
Section: Introductioncontrasting
confidence: 79%
“…Inspired by the enzyme-catalyzed oxidative halogenation in nature and our continuing interest and efforts in the utilization of cyclic peroxides, we are intrigued by the possibility of complementing the existing Hofmann–Löffler–Freytag-type processes by the combination of cyclic diacyl peroxides and diverse halide salts. We speculated that such proposed halogenating reagents (Figure ) could increase the efficiency of Hofmann–Löffler–Freytag-type reactions by two potential pathways: increasing the reactivity of halogenating reagent by the existence of the intramolecular benzoates, or influencing the conformation of the substrates to favor reactivity and selectivity by intermolecular force.…”
Section: Introductioncontrasting
confidence: 79%
“…4,5 The same is true of peroxides activated by conjugation, stereoelectronics, or strain. 6 For example, ozonides (1,2,4-trioxolanes) are reduced by glutathione, 7 and we have demonstrated rapid inactivation of the enzyme papain by an ozonide-containing dipeptide analog. 8 Selenoperoxidases are able to reduce strained cyclic peroxides.…”
Section: Introductionmentioning
confidence: 83%
“…Therefore, the synthesis and application of new peroxides with features that fulfill the above requirement remain a challenging task that must also take into account stability and safety. Additionally, simple manipulations of vicinal diacids as starting materials do not necessarily deliver the corresponding cyclic peroxides due to an inappropriate torsion angle or O–O bond distance as well as their inherent propensity for decarboxylation. , For instance, a phenyl group can readily be incorporated into P3 ; however, the resulting peroxide P5 is unstable and gradually decomposes at room temperature. The low stability of P5 could be attributed to the shortened O–O bond that increases the electrostatic repulsion of the peroxy oxygen lone pairs (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…The low stability of P5 could be attributed to the shortened O–O bond that increases the electrostatic repulsion of the peroxy oxygen lone pairs (Scheme ). , Furthermore, the shortened O–O bond in P5 implies a higher conjugation between the carbonyl group and peroxy oxygen that increases its electron density. It was reported that the increase in the ring strain (CO–C–CO angles) of the peroxide directly translates into increased reactivity .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation